An Evaluation of the Antibacterial, Anti-Giardial, Anticancer and Toxicity Properties of Selected Nut Extracts - Lebaratoux, Pauline; Sirdaarta, Joseph; Rayan, Paran; McDonnell, Pauline Ann; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Foods with high oil and fatty acid contents have been linked with a variety of medicinal properties including bacterial growth inhibition, anti-Giardial activity and the inhibition of cancer cell proliferation. Almond, cashew, hazelnut and walnut contain very high fatty acid contents. Despite this, these nuts have not been adequately screened for medicinal properties. Materials and Methods: Almond, cashew, hazelnut and walnut powders were extracted and tested for antimicrobial activity using modified disc diffusion and MIC methods. Inhibitory activity against the gastrointestinal protozoal parasite Giardia duodenalis and against CaCo2 cancer cells were evaluated using colorimetric cell proliferation assays. Toxicity was evalu- ated using an Artemia franciscana nauplii bioassay. Results: The methanolic almond and walnut solvent extractions displayed broad spectrum growth inhibitory activity, inhibiting the growth of 100% and 7 of the 11 (64%) bacterial strains tested respectively. The methanolic walnut extract was a particularly potent growth inhibitor, with MIC values of ~1000 µg/mL, 700 µg/mL and 800 µg/mL against A. baylyi, P. mirabilis and P. vulgaris respectively. The methanolic almond extract also had moderate to inhibitory activity against E. coli (MIC ~2000 µg/mL), P. mirabilis and P. vulgaris (both ~2500 µg/mL). The methanolic cashew and hazelnut extracts were moderate inhibitors of E. coli growth (~2500 and 1250 µg/mL respectively). The meth- anolic almond extract was also a potent inhibitor of G. duodenalis prolifera- tion (IC50 878 µg/mL). All extracts were ineffective at blocking the growth of the colorectal cancer cell line CaCo2. Instead, most of the extracts sub- stantially stimulated proliferation. All of the nut extracts were non-toxic in the Artemia nauplii bioassay. Conclusion: The bacterial growth inhibitory activities of the methanolic almond and walnut extracts, the anti-Giardial activity of the methanolic almond extract and their lack of toxicity indicates the potential of these extracts in the discovery and development of new natural antibiotic agents.
Keywords: Antibacterial activity; Giardia duodenalis; Anti-proliferative activity; CaCo2; Anticancer activity; Artemia; Toxicity.